Characterization of Donor Genome Segments of BC2 and BC4 Way Rarem x Oryzica Llanos-5 Progenies Detected by SNP Markers - Wening Enggarini; Surjono H. Sudjahjo; Trikoesoemaningtyas Trikoesoemaningtyas; Sriani Sujiprihati; Utut Widyastuti; Kurniawan R. Trijatmiko; Sugiono Moeljopawiro; Masdiar Bustamam; Casiana V. Cruz (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2012)
Plant breedersmake a succession of backcrosses to introgress a characterfrom a donor parent into genomic background of a recurrentparent. In several backcrossing, the proportion of a genometends to return almost fully to recurrent parent, except thesmall donor genome segment harboring the character ofinterest. The estimation of the proportion donor segmentthrough backcross generations has been analyzedtheoretically using complex mathematical simulations. Inthis study, the proportion of donor introgression segmentswere directly analyzed in advanced backcross populations,BC2F7 and BC4F2. The analysis was done by using a set ofsingle nucleotide polymorphism (SNP) markers covering theentire rice genome. Of the 384 SNP markers we found 124markers which provide polymorphism between recurrentparent, Way Rarem and Oryzica Llanos-5 as donor parent.But only 55 SNP markers could detect Oryzica Llanos-5alleles in BC2F7 and BC4F2 progenies. The result of thisanalysis demonstrated that the average of donor segmentnumber was 14.5 in BC2F7 and 12.3 in BC4F2. It was reduced15% from BC2F7 to BC4F2. The average of donor segmentlength was 31.2 cM (centiMorgan) in BC2F7 and 8.79 cM inBC4F2. It was decreased 72% during twice backcrossing. Theaverage of donor genome size was 343.95 cM in BC2F7 and71.35 cM in BC4F2, which means there was 79% decreasefrom BC2F7 to BC4F2. These results offered a simple methodto describe the proportion of target genome segment fromdonor parent. It was required as one of the main selectioncriteria in backcross programs.